Interaction between ataxin-2 binding protein 1 and cubitus-interruptus during wing development in drosophila - Usha, N.; Shashidhara, L. S. (Developmental Biology, 2010)
Animal growth and development is dependent on reiterative use of key signaling pathways such as Hedgehog (Hh) pathway. It is widely believed that Cubitus-interruptus (Ci) mediates all functions of Hh pathway. Here we report that CG32062, the Drosophila homologue of Ataxin-2 Binding Protein 1 (dA2BP1), functions as a cofactor of Ci to specify intervein region between L3 and L4 veins of the adult wing. Specifically, Ci-mediated transactivation of knot/collier (kn) in this region of the developing wing imaginal disc is dependent on dA2BP1 function. Protein interaction studies and chromatin-immunoprecipiation experiments suggest that Ci helps dA2BP1 to bind kn promoter, which in turn may help Ci to activate kn expression. These results suggest a mechanism by which Ci may activate targets such as kn, which do not have classical Ci/Gli-binding sites. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: CG32062; Collier; Hedgehog; Knot; SCA2